2020
DOI: 10.3390/ijerph17217938
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Implementation of a Clinical Practice Guideline for Homeless Health

Abstract: Clinical practice guidelines can improve the clinical and social care for marginalized populations, thereby improving health equity. The aim of this study is to identify determinants of guideline implementation from the perspective of patients and practitioner stakeholders for a homeless health guideline. We completed a mixed-method study to identify determinants of equitable implementation of homeless health guidelines, focusing on the Grading of Recommendations Assessment, Development and Evaluation Feasibil… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
21
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 19 publications
(23 citation statements)
references
References 38 publications
1
21
0
1
Order By: Relevance
“…These recommendations acknowledge the necessity of providing wraparound services in the primary care environment. The provision of housing is commonly regarded in the literature as the highest yield intervention for improving healthcare in individuals experiencing homelessness, which is also consistent with our findings (Magwood et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These recommendations acknowledge the necessity of providing wraparound services in the primary care environment. The provision of housing is commonly regarded in the literature as the highest yield intervention for improving healthcare in individuals experiencing homelessness, which is also consistent with our findings (Magwood et al, 2020).…”
Section: Discussionsupporting
confidence: 92%
“…These services have been incorporated successfully using a "one-stop-shop" strategy for different types of health and social care, or through the use of an outreach model of care. This concept was reported as a strength of many healthcare interventions targeted to individuals experiencing homelessness (Kertesz et al, 2021;Luchenski et al, 2018;Magwood et al, 2020). In a program serving veterans who are homeless, comparing regular health services to an integrated program that included primary care, social services, and mental health services demonstrated that patients who attended the integrated service had higher usage of primary care services and reduced usage of emergency services (McGuire et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
“…For example, people experiencing homelessness or vulnerable housing are often marginalized and are known to face barriers to accessing appropriate healthcare services ( 9 ). Although changes have been recommended in the complex health systems, so that it should be more equitable, more sensitive and empathic, and more informed about the traumatic situations experienced by homeless people, barriers related to cultural aspects are barely mentioned in those key documents ( 116 118 ). Similar patterns can be seen in the studies of other conditions of vulnerability and adverse circumstances that apparently seem disconnected from their own cultural aspects or they seem irrelevant for health equity ( 119 ).…”
Section: Discussionmentioning
confidence: 99%
“…Due to the milieu-speci c characteristics affecting the care and treatment of homeless people, guidelines should be developed to support doctors in their diagnostic and therapeutic approach. Magwood et al (2020) [28] developed criteria for "Clinical Practice Guideline for Homeless Health" which address the upstream social and health needs, as well as the downstream health consequences of inadequate housing. Speci cally, the kind of interventions indicated include the provision of supportive housing, income support and case management.…”
Section: Implications For the Health Systemmentioning
confidence: 99%